Autowaves in the moving excitable media - Davydov, V.A.; Davydov, N.V.; Morozov, V.G.; Stolyarov, M.N.; Yamaguchi, T. (Condensed Matter Physics, 2004)
Within the framework of kinematic theory of autowaves we suggest a method for analytic description of stationary autowave structures appearing at the boundary between the moving and fixed excitable media. The front breakdown phenomenon is predicted for such structures. Autowave refraction and, particulary, one-side “total reflection” at the boundary is considered. The obtained analytical results are confirmed by computer simulations. Prospects of the proposed method for further studies of autowave dynamics in the moving excitable media are discussed. В рамках кінематичної теорії автохвиль запропоновано метод для аналітичного опису стаціонарних автохвильових структур, що виникають на межі між рухомим та нерухомим збудженими середовищами. Передбачено явище розриву фронту автохвилі в таких структурах. Розглядається заломлення автохвилі та одностороннє “повне відбиття”на границі. Отримані аналітичні результати знайшли своє підтвердження при комп’ютерному моделюванні. Обговорюються перспективи застосування запропонованого методу для подальшого дослідження автохвильової динаміки в рухомих середовищах, що збуджуються.